2011
DOI: 10.1007/s13157-011-0181-8
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Trends of Five Plant Litter Types in Mitigated and Reference Wetlands in West Virginia, USA

Abstract: Decomposition of organic matter in wetlands is linked to numerous wetland processes, making it a useful metric to assess wetland function. We measured plant litter decomposition rates in three mitigated and three reference wetlands located in the Allegheny Mountains of West Virginia, from 2007 to 2009. Four common wetland species were used: broadleaf cattail (Typha latifolia L.), common rush (Juncus effusus L.), brookside alder (Alnus serrulata (Ait.)Willd.), and reed canary grass (Phalaris arundinacea L.). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…We used R 2.10.1 (R Development Core Team 2009) for all analyses. Decomposition rates were similar between mitigation and reference wetlands (Gingerich & Anderson 2011). Student's t-test was used to compare averages of environmental variables in mitigation and reference wetlands.…”
Section: Comparison Of Wetlandsmentioning
confidence: 79%
See 1 more Smart Citation
“…We used R 2.10.1 (R Development Core Team 2009) for all analyses. Decomposition rates were similar between mitigation and reference wetlands (Gingerich & Anderson 2011). Student's t-test was used to compare averages of environmental variables in mitigation and reference wetlands.…”
Section: Comparison Of Wetlandsmentioning
confidence: 79%
“…Decomposition rate constants were similar between mitigation and reference wetlands (Gingerich & Anderson 2011); therefore, wetland type was not included as a model variable. Ten of the models were single variable models (e.g., k D AT).…”
Section: Model Selectionmentioning
confidence: 99%
“…(), for example, Carex lyngbyei . Reed canarygrass has a faster decomposition rate than Typha latifolia (common cattail), Juncus effusus (soft rush), and Alnus rubra (red alder) leaves (Gingerich and Anderson ), which are common elsewhere including other parts of the Columbia River estuary. Additionally, the model only removes POM via physical means (erosion and transport), which are governed by fluid motion, and produces the greatest velocity and potential for erosion in the channels.…”
Section: Discussionmentioning
confidence: 99%
“…After hydrological connection, the KF site became dominated by reed canarygrass, a species that develops thick, tough mats that may be more recalcitrant to mobilization (Griffiths et al 2012) than those dominating sites studied by Simenstad et al (1990) and Kistritz et al (1983), for example, Carex lyngbyei. Reed canarygrass has a faster decomposition rate than Typha latifolia (common cattail), Juncus effusus (soft rush), and Alnus rubra (red alder) leaves (Gingerich and Anderson 2011), which are common elsewhere including other parts of the Columbia River estuary. Additionally, the model only removes POM via physical means (erosion and transport), which are governed by fluid motion, and produces the greatest velocity and potential for erosion in the channels.…”
Section: Marsh Plant Communitymentioning
confidence: 99%
“…Among the few lentic studies to address this question, results have demonstrated additive, synergistic, and antagonistic outcomes (Schädler et al. , Gingerich and Anderson , b, Stoler and Relyea , Liu et al. , Zhang et al.…”
Section: Theme 3: Effects Of Leaf Litter Mixingmentioning
confidence: 99%